EVALUTION OF ANTIMICROBIAL ACTIVITY OF PARTIAL PURIFIED BACTERIOCIN FROM LOCAL ISOLATE OF BACILLUS LICHENIFORIMS HJ2020 MT192715.1 - & Auda, Jebur (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to produce bacteriocin  from Bacillus. licheniformis  isolated from local soil of corn and sunflower  fields and using  as  antimicrobial agent . Fourteen  of  local  isolates  of Bacillus sp. were obtained and  ability of these  isolates  for growth on Brain heart infusion agar (BHI) at 550C were tested. Isolate C4   was revealed  high  growth density in comparison with other isolates.  Isolate C4 was identified as Bacillus licheniformis according to  morphological, cultural and biochemical tests, Moreover genetic analysis  for 16S rRNA gene and  given accession number  MT192715.1 in GenBank of NCBI . Production of bacteriocin  from this isolate was carried out in Luria Broth (LB) and  partially  purified  by precipitation with 30-70 % saturation of ammonium sulfate followed by concentrated using poly ethylene glycol (PEG).The antimicrobial activity of partially purified  bacteriocin was assayed  against many species of food spoilage microorganism. Results were  revealed  that anitimicrobial activity of bacteriocin were between (0 - 360 ) units / ml. Stability of antimicrobial activity of partially purified bacteriocin toward Staphylococcus aureus were tested  after incubation at different values of pH, temperature and some of enzyme which included  proteolytic enzymes, α-amylase and lipase .The results indicated that residual inhibition activity of bacteriocin  were varied according to conditions of  incubation  and type  of  treatment .